BS EN IEC 61755-3-8. Fibre optic interconnecting devices and passive components. Connector optical interfaces. Part 3-8. Connector parameters of non-dispersion shifted single mode physically contacting fibres. Angled 2, 5 mm and 1, 25 mm diameter cylindrical composite ferrules using titanium as fibre surrounding material (22nd January 2021) - British Standards Institution
No abstract available